Pengaruh media sosial terhadap interaksi sosial remaja di era digital - Farikha, Umi (Maliki Interdisciplinary Journal, 2025)
Social media is a highly influential social phenomenon in the lives of teenagers in the digital age. This article aims to comprehensively examine how social media use affects teenagers' social interactions, both positively and negatively. Through a literature review, it was found that social media provides opportunities to expand social networks, foster creativity, and support informal learning. However, excessive use also has the potential to reduce the quality of face-to-face communication, increase the risk of social isolation, cyberbullying, and mental health problems. Therefore, the role of families, schools, and communities is important in guiding healthy social media use. This article emphasizes that a balance between the virtual world and the real world is key to shaping adaptive social interactions among teenagers.